Harnessing insects for novel feed products in agricultural waste management: Review - Caisin, Larisa; Scripnic, Elena; Malenchi, Dumitru; Bivol, Ludmila (Edelweiss Applied Science and Technology, 2025)
The growing demand for sustainable protein in animal production has increased interest in insects as alternative feed ingredients, especially in poultry nutrition. Insects are nutrient-rich, providing high-quality protein, lipids, essential amino acids, and bioactive compounds that support growth, health, and feed efficiency. Black soldier fly larvae (Hermetia illucens), mealworms (Tenebrio molitor), and crickets (Acheta domesticus) are among the most studied species, showing potential to replace conventional protein sources such as soybean meal and fishmeal. Insect-based feeds improve nutrient utilization, gut health, and reduce environmental impact by valorizing agricultural and food by-products, contributing to circular economy models. This review evaluates the nutritional, environmental, and regulatory aspects of insect-based feeds. A comprehensive synthesis of recent literature was conducted, focusing on composition, functional properties, safety, and sustainability. Findings indicate that Hermetia illucens, Tenebrio molitor, and Acheta domesticus provide high-quality protein and bioactive compounds that enhance poultry growth performance and feed efficiency. Insect utilization transforms organic waste into protein-rich biomass, reducing environmental impact. However, large-scale adoption is limited by production costs, regulatory inconsistencies, and safety concerns. Practical implications stress the need for standardized safety and quality frameworks, cost-effective mass-rearing technologies, and long-term feeding trials. Overall, insect farming offers a sustainable strategy to enhance resource efficiency, food security, and environmental resilience in animal production.